All economic ideas are equal, but some are more equal than others: A differentiated perspective on macroprudential ideas and their implementation - Edin Ibrocevic; Matthias Thiemann (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2018)
In this study we investigate which economic ideas were prevalent in the macroprudential discourse post-crises in order to understand the availability of ideas for reform minded agents. We base our analysis on new findings in the field of ideational shifts and regulatory science, which posit that change-agents engage with new ideas pragmatically and strategically in their effort to have their economic ideas institutionalized. We argue that in these epistemic battles over new regulation, scientific backing by academia is the key resource determining the outcome. We show that the present reforms implemented internationally follow this pattern. In our analysis we contrast the entire discourse on systemic risk and macroprudential regulation with Borio's initial 2003 proposal for a macroprudential framework. We find that mostly cross-sectional measures targeted towards increasing the resilience of the financial system rather than inter-temporal measures dampening the financial cycle have been implemented. We provide evidence for the lacking support of new macroprudential thinking within academia and argue that this is partially responsible for the lack of anti-cyclical macroprudential regulation. Most worryingly, the financial cycle is largely absent in the academic discourse and is only tacitly assumed instead of fully fledged out in technocratic discourses, pointing to the possibility that no anti-cyclical measures will be forthcoming.
urn:nbn:de:hebis:30:3-466809
Keywords: 330